EFEKTIVITAS MODEL ROLE PLAYING DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V - Wahyuni Syafitri Burhan; Dedek Oktavia Nasution; Almira Amir (JURNAL MathEdu (Mathematic Education Journal), 2026)
This research is motivated by the low mathematics learning outcomes of elementary school students caused by teacher-centered learning and lack of active student involvement. Therefore, an innovative learning model is needed that is able to increase students' understanding of concepts and activeness, one of which is through the role playing model. This study aims to determine the effectiveness of the application of the role playing model in improving the mathematics learning outcomes of grade V students. Data collection techniques are carried out through tests, observations, and documentation. The results of the study showed an increase in student learning outcomes, marked by the percentage of learning completeness that increased from 48% in the first cycle to 80% in the second cycle. In addition, teacher activities and student involvement in learning have also increased significantly. These findings show that the application of the role playing model is effective in improving mathematics learning outcomes and encouraging student activity and confidence. Thus, this model is suitable as an alternative in learning mathematics in elementary school. Keywords— role playing, learning outcomes, math, student activities, innovative learning